Population Ecology, Ethnobotny and Distribution of Podophyllum hexandrum Royle an Endangered Medicinal Plant in Suru Valley, Ladakh, Jammu & Kashmir, India - Rinchen, Tsewang; Pant, Shreekar (Indian Forester, 2017)
Present study is conducted to investigate the population ecology, distribution and ethnobotany of the Podophyllum species as a foundation for its conservation. Fifty sites having two habitats were surveyed intensively but, only in seventeen sites the species is present more over the species is present only in five transects out of eleven transects in the valley. The impact of grazing, over exploitation, specific habitat, unscientific collection and lack of its seed disseminator, indicated that it may soon be extirpated from the restricted areas of Suru Valley. This study will provide a template for conservation of the remaining number of the species in the Suru valley and other restricted locations of IHR where the species is at risk.